A Dynamic Displacement Measurement Experiment Using Self-Mixing Laser Diode Interferometry - De Lucena, Samuel E. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2024)
This paper presents the design and evaluation of a laser-based relative dynamic displacement measurement using the self-mixing laser diode technique. A 980-nm wavelength near infrared laser diode was driven under constant current regime, while the monitor photodiode current was processed by a transimpedance amplifier to allow detection and recording of the interference pattern due to the oscillation of a target (loudspeaker diaphragm) located just in front of the laser diode package. Several experiments were carried out, by changing the frequency and amplitude of the target oscillation. In spite of the instrumentation simplicity, the interference patterns recorded for every experiment made its adequacy clear enough.
Keywords: controlled current source; dynamic displacement measurement; interferogram; interferometry; laser diode; monitor photodiode; self-mixing laser diode interferometry; velocity measurement; vibration measurement